2011
DOI: 10.1007/s00256-011-1199-y
|View full text |Cite
|
Sign up to set email alerts
|

MRI findings, patterns of disease distribution, and muscle fat fraction calculation in five patients with Charcot-Marie-Tooth type 2 F disease

Abstract: We described the pattern of muscle involvement and disease progression in a family with CMT disease type 2 F. GRE dual-echo dual-flip angle MRI technique is a valuable technique to obtain a rapid quantification of MFF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
58
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(64 citation statements)
references
References 27 publications
6
58
0
Order By: Relevance
“…Our MR imaging was enhanced by the use of a 2-point Dixon technique, which after post-processing allows for quantitative, as opposed to qualitative, assessment of fatty infiltration of musculature. Quantitative fat-fraction MRI of skeletal muscle already shows promise in other neuromuscular disorders, including Duchene muscular dystrophy and Charcot-Marie-Tooth [18][19][20]. However, true quantitative MR assessment of lingual fat in patients with neuromuscular disorders, including GSD II and GSD III, has not yet been reported to our knowledge, though quantitative fat-fraction imaging of the normal tongue has been performed [21].…”
Section: Discussionmentioning
confidence: 94%
“…Our MR imaging was enhanced by the use of a 2-point Dixon technique, which after post-processing allows for quantitative, as opposed to qualitative, assessment of fatty infiltration of musculature. Quantitative fat-fraction MRI of skeletal muscle already shows promise in other neuromuscular disorders, including Duchene muscular dystrophy and Charcot-Marie-Tooth [18][19][20]. However, true quantitative MR assessment of lingual fat in patients with neuromuscular disorders, including GSD II and GSD III, has not yet been reported to our knowledge, though quantitative fat-fraction imaging of the normal tongue has been performed [21].…”
Section: Discussionmentioning
confidence: 94%
“…Dual-echo dual-flip angle SPGR is a rapid technique available on all routine MRI systems. Most recently, the same author applied this technique in five patients with late-onset Charcot-Marie-Tooth disease type 2, and found that it is a valuable tool for rapid MFF calculation [17].…”
Section: Discussionmentioning
confidence: 98%
“…It has been well documented that the amount of intramuscular fat is an accurate marker of disease progression [1], and it also sensitively correlates with both patient age and clinical stage [10][11][12][13][14][15][16][17][18][19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6) [12,39]. Axial T1-weighted images through the lower thighs may show bilateral fatty infiltration of the posterior compartments, with the anterior compartment showing delayed involvement [40]. On T2-weighted images, the affected nerve appears hyperintense and diffusely enlarged with uniform prominence of the fascicles.…”
Section: Charcot-marie-tooth Diseasementioning
confidence: 98%